2003
DOI: 10.1261/rna.5940703
|View full text |Cite
|
Sign up to set email alerts
|

A role for the exosome in the in vivo degradation of unstable mRNAs

Abstract: In mammals, the mRNAs encoding many proteins involved in inflammation bear destabilizing AU-rich elements (AREs) in the 3-untranslated region. The exosome, a complex of 3 → 5 exonucleases, is rate limiting in the destruction of such mRNAs in a mammalian in vitro system, but a role in vivo has not been demonstrated. The phenomenon of ARE-mediated degradation also occurs in the protist parasite Trypanosoma brucei. Messenger RNAs with 3-untranslated region U-rich elements, which strongly resemble AREs, are extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 41 publications
(72 reference statements)
3
80
0
Order By: Relevance
“…Exosomes mediate cell communication through fusion between the exosome membrane and the plasma membrane of the recipient cell, a process that requires the integrity of the exosome membrane (24). We confirmed this in our studies by showing that exosomes that had been disrupted had no effect on monocyte survival.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Exosomes mediate cell communication through fusion between the exosome membrane and the plasma membrane of the recipient cell, a process that requires the integrity of the exosome membrane (24). We confirmed this in our studies by showing that exosomes that had been disrupted had no effect on monocyte survival.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies suggested that the efficiency of exosomes in transport of functional biomolecules relies on their vesicle integrity (24). To validate the necessity of exosome integrity for monocyte survival, we disrupted MCF-7-derived exosomes by repeated freezing and thawing or by permeabilization of the exosome membrane with 0.1% saponin (25).…”
Section: Characterization Of Cancer Cell-derived Exosomes and Theirmentioning
confidence: 99%
“…1). It is noteworthy that Rrp4 and Csl4 are conserved in the exosomes of Archaea and Eukarya [3,[16][17][18], suggesting important differential roles for these proteins, most probably in substrate selection. The archaeal exosome is a suitable system for analysis of the functions of Rrp4 and Csl4: in contrast to the eukaryotic exosome, active protein complexes with homotrimeric Rrp4 or Csl4 caps bound to the hexameric core can be reconstituted [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of Rrp6 resides in the nucleus in S. cerevisiae, evidence suggests its presence in the cytoplasm in humans, T. brucei and A. thaliana. [1][2][3] In S. cerevisiae, where Rrp6 has been studied most extensively, deletion of the sole copy of its gene (RRP6) causes a slow growth phenotype at 30 o C and extremely poor growth at 37 o C. 4 Nevertheless, the fact that deletion of any of the other exosome genes causes lethality has made the use of rrp6-∆ strains a valuable tool for the study of exosome defects in nuclear RNA processing.…”
Section: Introductionmentioning
confidence: 99%